The intentional leader : how inner authority can unleash strong leadership - Hebert, Tim (Ascent Audio, 2022)
In The Intentional Leader, Tim Hebert explores the various actions that define and shape leadership. From those decisive moments in which a difficult decision must be made, to the unguarded moments when our emotional, authentic selves manifest themselves for better or worse. We have an overabundance of "leaders" in our world today. But those who truly stand out are the ones who lead in a way that inspires employees to rally behind the organizational cause-whether that be developing cutting-edge technologies or selling fast food. This is Intentional Leadership. Tim defines this as clear, aligned, compassionate guidance delivered with a strong core ideology. It's responsive, not reactionary. It's inclusive, not prejudiced. It's transformational, not transactional. It's innovative, daring, and inspirational leadership. Drawing upon his extensive experience as a business leader and consultant, Tim Hebert provides practical advice and broadly applicable guidance that will bolster business leaders across all industries. With an engaging combination of high-profile case studies, firsthand experiences, and enlightening research, The Intentional Leader is the essential guide to cultivating an authentic, effective, and sustainable approach to leadership.